Non-inflammatory Chronic Pelvic Pain Syndrome (Scrotal pain) in a infertile man with non-palpable Testicular Seminoma and Bilateral Testicular Microlithiasis. Case study - I. A. Korneyev (Вестник урологии)
A 26-year-old patient with cryptozoospermia turned to the International Center for Reproductive Medicine for infertility. The man underwent surgical treatment for right-sided cryptorchidism in childhood. Subsequently, he was repeatedly examined and treated for scrotal pain. An ultrasound examination of the scrotum revealed bilateral testicular microlithiasis and signs of neoplasm of the left testicle that was not detected by palpation. Based on the research data, the patient underwent left orchifuniculectomy. Based on a histological examination, the diagnosis was established: a mixed germ cell tumor seminoma and teratoma against the background of intratubular germ cell neoplasia. A case from practice allows us to justify the expansion of indications for ultrasound of the scrotum in the non-inflammatory chronic pelvic pain syndrome (scrotal pain).